Using scaffolding strategies to improve formative assessment practice in higher education. Issue 3 (11th April 2022) - Kruiper, Stephanie M. A.; Leenknecht, Martijn J. M.; Slof, Bert
Abstract: Despite the increasing popularity of formative assessment as an instructional tool, teachers find it difficult to implement formative assessment strategies in their practice. To address this we developed a training programme based on formative assessment and scaffolding literature. A quasi-experimental design was utilised to examine the programme's usefulness; 8 teachers in higher education received the training and eight teachers did not. A questionnaire ( N  = 260) was administered before and after the training to determine students' perceptions of their teachers' adaptive behaviour. The trained teachers also participated in an interview about the usefulness of the training. Although no significant interaction effects between time and group were found, results over time reveal that both trained and untrained teachers showed more adaptive behaviour by providing more challenge when needed. Both groups of teachers also showed more non-adaptive behaviour since they gave more support and challenge than needed and became less supportive when students needed support. Results between groups indicate that trained teachers showed more adaptive behaviour than untrained teachers. Interview results indicate that teachers reviewed the training positively and reported scaffolding theory as a useful addition. Teachers requested more time and support to implement newly learned strategies in daily practice.